Population pharmacokinetics of intravenously and orally administered docetaxel with or without co-administration of ritonavir in patients with advanced cancer - Koolen, Stijn L W (Blackwell Science Inc, 2010)
AIM: Docetaxel has a low oral bioavailability due to affinity for P-glycoprotein and cytochrome P450 (CYP) 3A4 enzymes. Inhibition of the CYP3A4 enzymes by ritonavir resulted in increased oral bioavailability. The aim of this study was to develop a population pharmacokinetic (PK) model and to evaluate and quantify the influence of ritonavir on the PK of docetaxel. METHODS: Data from two clinical trials were included in the data analysis, in which docetaxel (75 mg m(−2) or 100 mg) had been administered intravenously or orally (10 mg or 100 mg) with or without co-administration of oral ritonavir (100 mg). Population modelling was performed using non-linear mixed effects modelling. A three-compartment model was used to describe the i.v. data. PK data after oral administration, with or without co-administration of ritonavir, were incorporated into the model. RESULTS: Gut bioavailability of docetaxel increased approximately two-fold from 19 to 39% (CV 13%) with ritonavir co-administration. The hepatic extraction ratio and the elimination rate of docetaxel were best described by estimating the intrinsic clearance. Ritonavir was found to inhibit in a concentration dependent manner the intrinsic clearance of docetaxel, which was described by an inhibition constant of 0.028 µg ml(−1) (CV 36%). A maximum inhibition of docetaxel clearance of more then 90% was reached. CONCLUSIONS: A PK model describing both the PK of orally and intravenously administered docetaxel in combination with ritonavir, was successfully developed. Co-administration of ritonavir lead to increased oral absorption and reduced elimination rate of docetaxel.